Rounding up the annual ryegrass genome: High-quality reference genome of Lolium rigidum - Paril, Jefferson; Pandey, Gunjan; Barnett, Emma M.; Rane, Rahul V.; Court, Leon; Walsh, Thomas; Fournier-Level, Alexandre (Frontiers in Genetics, 2022)
The genome of the major agricultural weed species, annual ryegrass (Lolium rigidum) was assembled, annotated and analysed. Annual ryegrass is a major weed in grain cropping, and has the remarkable capacity to evolve resistance to herbicides with various modes of action. The chromosome-level assembly was achieved using short- and long-read sequencing in combination with Hi-C mapping. The assembly size is 2.44 Gb with N50 = 361.79 Mb across 1,764 scaffolds where the seven longest sequences correspond to the seven chromosomes. Genome completeness assessed through BUSCO returned a 99.8% score for complete (unique and duplicated) and fragmented genes using the Viridiplantae set. We found evidence for the expansion of herbicide resistance-related gene families including detoxification genes. The reference genome of L. rigidum is a critical asset for leveraging genetic information for the management of this highly problematic weed species.